Study on GaN nanostructures: Growth and the suppression of the yellow emission. (July 2018) - Wang, Ting; Chen, Fei; Ji, Xiaohong; Zhang, Qinyuan
Abstract: GaN nanostructures were synthesized via a simple chemical vapor deposition using Ga2 O3 and NH3 as precursors. Structural and morphological properties were systematically characterized by field emission scanning electron microscopy, X-ray diffractometer, transmission electron microscopy, and Raman spectroscopy. The configuration of GaN nanostructures was found to be strongly dependent on the growth temperature and the NH3 flow rate. Photoluminescence analysis revealed that all the fabricated GaN NSs exhibited a strong ultra-violet emission (∼364 nm), and the yellow emission of GaN nanorods can be suppressed at appropriate III/V ratio. The suppression of the yellow emission was attributed to the low density of surface or the VGa defect. The work demonstrates that the GaN nanostructures have potential applications in the optoelectronic and nanoelectronic devices. Highlights: The manifold GaN nanostructures are grown by Au catalytic CVD method. The configuration of GaN nanostructures is strongly dependent on III/V ratio. GaN nanostructures exhibit strong UV PL emission with suppressed visible emission.